The Blockchain and Increasing Cooperative Efficacy. - NAIR, MALAVIKA; SUTTER, DANIEL (Independent Review)
The article evaluates the economic impacts of blockchain technology. Topics mentioned include the application of public goods argument for government, the assessment of the ability of government and voluntary sector in producing different individual public goods, the explanation of the blockchain, and the examples of blockchain that increases cooperative efficacy.